Differences in Effective Duration of Cold Compress Administration on Reducing Pain Intensity in Fracture Patients - Masrida Hanum; Dudut Tanjung; Yetty Mahcrina (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Fracture is one of the problems in health care centers around the world. The condition of the tissue around the fracture will experience damage to its integrity so that it can cause pain, trauma, joint stiffness, and musculoskeletal disorders. Pain is a sensory or emotional experience related to tissue damage. Sharp and stabbing pain is felt due to bone infection due to muscle spasms or pressure on sensory nerves. Non-pharmacological therapies include cold compresses that can reduce pain, reduce inflammatory responses, and reduce blood flow and reduce edema. This therapy is more effectiveand easy to do independently by patients. Cold pack for compresses are also useful for reducing muscle tension and reducing swelling so that patients are more comfortable and relaxed. This study aims to assess the difference in the duration of cold compresses using cold packs on reducing the intensity of acute pain in fracture patients at the Haji Adam Malik Central General Hospital. The research method is Quasi-Experimental with a pretest, posttest group design approach. Sampling using the consecutive sampling technique so that 66 respondents were obtained. The research instrument used the Numeric Rating Scale. The data were analyzed using the Wilcoxon and Mann Whitney U tests. The results showed that the mean value for the 20 minute compress group was 23.85, while the mean value for the 30 minute compress group was 43.15 with a p value <0.05. It can be concluded that giving a cold compress for 30 minutes is much more effective than giving a cold compress for 20 minutes. It is hoped that nurses in providing nursing care can apply a cold compress for 30 minutes using a cold pack as an independent nursing action in managing fracture pain in the hospital. Keywords: Cold Pack, Pain, Fracture